Acid Hydrolysis of Gluten Enhances the Skin Sensitizing Potential and Drives Diversification of IgE Reactivity to Unmodified Gluten Proteins. Issue 23 (27th October 2021) - Ballegaard, Anne‐Sofie Ravn; Castan, Laure; Larsen, Jeppe Madura; Piras, Cristian; Villemin, Clélia; Andersen, Daniel; Madsen, Charlotte Bernhard; Roncada, Paola; Brix, Susanne; Denery‐Papini, Sandra; Mazzucchelli, Gabriel; Bouchaud, Grégory; et al.
Abstract : Scope: Personal care products containing hydrolyzed gluten have been linked to spontaneous sensitization through the skin, however the impact of the hydrolysate characteristics on the sensitizing capacity is generally unknown. Methods and Results: The physicochemical properties of five different wheat‐derived gluten products (one unmodified, one enzyme hydrolyzed, and three acid hydrolyzed) are investigated, and the skin sensitizing capacity is determined in allergy‐prone Brown Norway rats. Acid hydrolyzed gluten products exhibited the strongest intrinsic sensitizing capacity via the skin. All hydrolyzed gluten products induced cross‐reactivity to unmodified gluten in the absence of oral tolerance to wheat, but were unable to break tolerance in animals on a wheat‐containing diet. Still, the degree of deamidation in acid hydrolyzed products is associated with product‐specific sensitization in wheat tolerant rats. Sensitization to acid hydrolyzed gluten products is associated with a more diverse IgE reactivity profile to unmodified gluten proteins compared to sensitization induced by unmodified gluten or enzyme hydrolyzed gluten. Conclusion: Acid hydrolysis enhances the skin sensitizing capacity of gluten and drives IgE reactivity to more gluten proteins. This property of acid hydrolyzed gluten may be related to the degree of product deamidation, and could be a strong trigger of wheat allergy in susceptible individuals. Abstract : Acid hydrolysis changes the physicochemical properties of gluten proteins leading to enhanced skin sensitizing capacity and broader IgE‐reactivity towards more proteins. This property of acid hydrolyzed gluten may be related to degree of product deamidation, and could be a strong trigger of wheat allergy in susceptible individuals. Yet, acid hydrolysis did not lead to a break of established oral tolerance to unmodified gluten.